Knowledge of nursing staff about patient care with infection caused by multidrug-resistant - Maria Cristina de Sousa Silva, Maria Eliete Batista Moura, Paula Roberta Silva Magalhães, Virlândia Raquel Macêdo dos Santos, Yvanise Cleisiane Costa dos Santos (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v4i2.2940